Peningkatan kemampuan komunikasi matematis dengan model project based learning berbantuan geogebra: Solusi inovatif pendidikan modern - Lismayanti, Neng; Hutajulu, Masta; Linda, Linda (IKIP Siliwangi, 2024)
This study aims to research the improvement of students' mathematical communication skills through the application of a project-based learning model supported by geogebra and conventional learning. The research method used is a quasi-experimental method with a non-equivalent control group design. The sample in the study was class VIII A with a total of 30 students and Class VIII B with a total of 30 students and the sample selection was not carried out randomly. The research instruments used for tests and non-tests are mathematical communication skills tests in the form of descriptions of 6 questions and questionnaires of student responses to the stages of the project-based learning model. This research procedure includes three main phases: preparation, implementation, and evaluation. The data processing technique uses two independent sample tests with the help of SPSS version 25. The results of this study indicate that the mathematical communication skills of students who use the project-based learning model with the help of geogebra increase significantly compared to conventional learning.